Financing of smart growth in less developed regions on the example of Poland - Dorota Murzyn (e-Finanse: Financial Internet Quarterly, 2018)
The aim of this paper is twofold. First, the smart growth concept is examined with a focus on challenges associated with applying this concept in the less developed regions. Second, the impact of EU structural funds on smart growth in Poland is analyzed at the regional level with a view to contributing to the debate on public intervention in this area. The research questions are as follows: 'Is the concept of smart growth, as postulated by the European Union, well suited to the less developed regions?' and 'Whether and to what extent do EU funds contribute to achieving smart growth in Poland?' Smart growth has accelerated after 2007, which could suggest a significant impact of EU structural funds, whose allocation to measures supporting innovative activity rose markedly after 2007. However, among the various factors influencing regional development processes, the impact of structural funds was not as strong as might be expected, which was confirmed by further analysis.
Keywords: F36; O11; O30; R11; 330; smart growth; regional development; EU structural funds; Europe 2020